Proceedings of the 2006 ACM/IEEE Symposium on Architecture for Networking and Communications Systems 2006
DOI: 10.1145/1185347.1185350
|View full text |Cite
|
Sign up to set email alerts
|

Towards an efficient switch architecture for high-radix switches

Abstract: The interconnection network plays a key role in the overall performance achieved by high performance computing systems, also contributing an increasing fraction of its cost and power consumption. Current trends in interconnection network technology suggest that high-radix switches will be preferred as networks will become smaller (in terms of switch count) with the associated savings in packet latency, cost, and power consumption. Unfortunately, current switch architectures have scalability problems that preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 18 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…One approach is to design directional-based smaller crossbars for x and y directions as in [12], [13] by increasing the input speedup. One potential problem with these approaches is that the same input cannot be directed to different direction when the opportunity may arise.…”
Section: B Dual Input Single Crossbarmentioning
confidence: 99%
“…One approach is to design directional-based smaller crossbars for x and y directions as in [12], [13] by increasing the input speedup. One potential problem with these approaches is that the same input cannot be directed to different direction when the opportunity may arise.…”
Section: B Dual Input Single Crossbarmentioning
confidence: 99%
“…Current trends in interconnection network technology suggest that high-radix switches will be preferred for savings in cost, packet latency, and power consumption [4,5]. With high-radix switches, the hop count in the network decreases.…”
Section: Introductionmentioning
confidence: 99%
“…With high-radix switches, the hop count in the network decreases. Additional benefits from high-radix switches are lower cost and lower power, as the total number of switches and links to build a network is reduced [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chaos switch decoupled X direction from Y direction. In [56] a hierarchical optimal implementation (Partitioned Crossbar Input Queued) of a crossbar is presented. In this paper it is shown that a partitioned crossbar is able to obtain higher switch efficiency than a conventional crossbar design.…”
Section: Switch Designmentioning
confidence: 99%